Temple Building in the Bible in Light of Mesopotamian and North-West Semitic Writings - Hurowitz, Victor (Avigdor) (1983)
in Hebrew; Diss.; Supervisors: M. Haran and A.Shaffer. Cf. JAOS 105 (1985) 21.